Communication between the state and citizens at the local level in the Republic of Belarus: current status and ways to improve - Kisialiova, Tatsiana М. (Journal of the Belarusian State University. Law, 2026)
In this article, the author explores the importance and problems of organising communication between local authorities and the population of local territories. The author analyses methods of communication, including the submission and review of appeals, citizen participation in local public debates, and interactions between deputies and voters. The author also substantiates the need to develop a communication framework for local authorities and the population of local territories.
Keywords: communication between the state and citizens; appeals of citizens; public discussions; reports of deputies to voters; local government; local self-government